2015
DOI: 10.1017/s0007114515000070
|View full text |Cite
|
Sign up to set email alerts
|

The combined impact of adherence to five lifestyle factors on all-cause, cancer and cardiovascular mortality: a prospective cohort study among Danish men and women

Abstract: Individual lifestyle factors have been associated with lifestyle diseases and premature mortality by an accumulating body of evidence. The impact of a combination of lifestyle factors on mortality has been investigated in several studies, but few have applied a simple index taking national guidelines into account. The objective of the present prospective cohort study was to investigate the combined impact of adherence to five lifestyle factors (smoking, alcohol intake, physical activity, waist circumference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 54 publications
4
77
0
Order By: Relevance
“…Interest in multiplex testing for breast cancer susceptibility may create a teachable moment that can be used by clinicians to counsel about behavior change. Health messages can include broadly applicable recommendations such as increasing fruit and vegetable intake and physical activity, healthy behaviors that are associated with decreases in incidence and mortality from cancer and other chronic disease (Kabat et al, 2015; Petersen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Interest in multiplex testing for breast cancer susceptibility may create a teachable moment that can be used by clinicians to counsel about behavior change. Health messages can include broadly applicable recommendations such as increasing fruit and vegetable intake and physical activity, healthy behaviors that are associated with decreases in incidence and mortality from cancer and other chronic disease (Kabat et al, 2015; Petersen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Loef et al found that those with at least four health behaviours had a 66% reduced risk of all-cause mortality [5]. In addition to all-cause mortality [6], lifestyle indexes have shown clear relationships with cancer risk [7–12], cardiovascular incidence and mortality [1216] and diabetes [17]. A recent study showed that combinations of risk factors had synergistic effects on all-cause mortality, where some risk combinations were more harmful than others [4].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent reductions in risk ranging from 27 to 68% over 10.5–24 years of follow-up were reported in those with the highest adherence to cancer prevention guidelines compared to the lowest adherence [20, 21, 2831]. Similarly, a significant p -trend was reported as adherence to cancer prevention guidelines increased in several studies [20, 29, 30]. A large proportion of all-cause mortality in cancer patients consists of deaths due to cardiovascular and pulmonary diseases [47].…”
Section: Discussionmentioning
confidence: 74%